Edukasi Terapi Musik Klasik Pada Lansia Hipertensi di Wilayah UPTD Puskesmas Gumawang Kabupaten Oku Timur - Parmin, Selamat; Safitri, Serli Wulan; Wulandari, Shindi (Yayasan Daarul Huda Kruengmane, 2023)
Hypertension is a condition characterized by an increase in blood pressure that exceeds the normal limit, namely blood pressure exceeding 140/90 mmHg. Classical music that is often used as a reference is Mozart's classical music because almost all of Mozart's works have high-frequency tones. This music therapy is carried out once a day for 3 days with a duration of 30 minutes using a cellphone with earphones that have been connected to classical music with a moderate volume to the respondents. This study aims to provide valuable experience regarding Classical Music Therapy on Reducing Blood Pressure in Elderly Hypertensives in the UPTD Gumawang Health Center Area, OKU Regency. The research design used was a quasi-experimental with a research design (two group pretest-posttest design). The sample for this community service was all hypertension sufferers at the UPTD Gumawang Health Center. Data analysis was carried out using the Wilcoxon test. Based on the results of the hypothesis test, a decrease in blood pressure before classical music therapy was 3.57, after 2.62 supported by a p-value of 0.000 <0.05 can be interpreted that classical music therapy education on reducing blood pressure in hypertension patients at the UPTD Gumawang Health Center. The conclusion from the results of education on classical music therapy is the realization of experience with hypertension in reducing blood pressure. Suggestions for this activity can be used as a sustainable intervention that can be used independently by hypertension patients through classical music therapy.